1998
DOI: 10.1176/jnp.10.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Is Not Depression

Abstract: If depression is associated with apathy, then they should be expressed together in different dementia syndromes and should co-occur at varying levels of disease severity. The authors performed a cross-sectional comparison of neuropsychiatric symptoms in 30 Alzheimer's disease, 28 frontotemporal dementia, 40 Parkinson's disease, 34 Huntington's disease, and 22 progressive supranuclear palsy patients, using a standardized rating scale (the Neuropsychiatric Inventory). Apathy did not correlate with depression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
418
3
22

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 589 publications
(475 citation statements)
references
References 35 publications
32
418
3
22
Order By: Relevance
“…78,143,144 Prevalence of apathy is substantially higher in neurodegenerative diseases with more prominent involvement of the prefrontal cortex and caudate nuclei: it is present in 60-90% of patients with progressive supranuclear palsy, 75-95% of patients with frontotemporal dementia, and 55-90% of patients with Huntington's disease. [145][146][147][148] In these diseases, apathy is one of the fi rst neuropsychiatric symptoms to appear, is predictive of disease onset, 149,150 and is more clearly distinguished from depression than it is in Parkinson's disease. [151][152][153] A consideration of the multidimensional nature of apathy, as presented in this Review, would be useful in understanding the major components of apathy in each of these neurodegenerative diseases.…”
Section: Apathy In the Wider Context Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…78,143,144 Prevalence of apathy is substantially higher in neurodegenerative diseases with more prominent involvement of the prefrontal cortex and caudate nuclei: it is present in 60-90% of patients with progressive supranuclear palsy, 75-95% of patients with frontotemporal dementia, and 55-90% of patients with Huntington's disease. [145][146][147][148] In these diseases, apathy is one of the fi rst neuropsychiatric symptoms to appear, is predictive of disease onset, 149,150 and is more clearly distinguished from depression than it is in Parkinson's disease. [151][152][153] A consideration of the multidimensional nature of apathy, as presented in this Review, would be useful in understanding the major components of apathy in each of these neurodegenerative diseases.…”
Section: Apathy In the Wider Context Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…In the literature, it has been demonstrated that apathy is associated with cognitive dysfunction [15,41,[43][44][45][46][47][48][49][50][51][52][53] (See table 2), depression [44-46, 50, 51, 53-56] and anxiety [57]. Although apathy and depression can co-exist in PD, several studies have found that apathy may occur in isolation in the absence of depression [15,45,46,51,53,56,[58][59][60].…”
Section: Apathymentioning
confidence: 99%
“…Although apathy and depression can co-exist in PD, several studies have found that apathy may occur in isolation in the absence of depression [15,45,46,51,53,56,[58][59][60].…”
Section: Apathymentioning
confidence: 99%
“…however, apathy can occur without depression in Ad and when depression and apathy co-occur in Ad patients, it has been shown that they are clinically and anatomically independent [20][21][22] . Indeed, in order to discriminate apathy from depression, several scales have been designed to quantify apathy, which wisely exclude symptoms such as sadness and negative thoughts, typically observed in depressive syndromes 15,[23][24][25][26][27] .…”
mentioning
confidence: 99%